Анализ эффективности процессов планирования электроснабжения в Харьковском регионе - Евчу, М. Н.; Иваницкий, Вадим Дорофеевич; Иваницкий, Е. В.; Старков, К. А. (НТУ "ХПИ", 2010)
Ефективність процесів електропостачання запропоновано оцінювати не тільки величиною помилки прогнозування, а й кількістю негативних і позитивних помилок, що вимірюються за методикою Тейла. Виконано аналіз планованих і фактичних добових обсягів електроспоживання в Харківському регіоні в 2008 і 2009 роках. Оцінено помилки переоцінки і недооцінки фактичних обсягів, обчислені складові загальної помилки і показано, що переважає помилка неповної коваріації прогнозованих і фактичних значень добових обсягів ринку споживачів АК "Харківобленерго".

The effectiveness of the processes of electricity supply was offered to assess not only with the magnitude of forecasting error, but with the number of negative and positive errors, measured by the method of Theil. The analysis of planned and actual daily volume of electricity in Kharkov region in 2008 and 2009 is realized. Errors of revaluation and underestimation of actual volumes are estimated, components of the general error are calculated and shown that the error of incomplete covariance for predicted and actual values of daily volumes of the market of consumers АК of "Kharkovo-blenergo" prevails.
Keywords: энергосбережение; рыночная экономика; диаграммы Тейла; электропотребление; потребители